Connecting Hydroxychloroquine In Vitro Antiviral Activity to In Vivo Concentration for Prediction of Antiviral Effect: A Critical Step in Treating Patients With Coronavirus Disease 2019. (21st May 2020) - Fan, Jianghong; Zhang, Xinyuan; Liu, Jiang; Yang, Yuching; Zheng, Nan; Liu, Qi; Bergman, Kimberly; Reynolds, Kellie; Huang, Shiew-Mei; Zhu, Hao; Wang, Yaning
Abstract: Translation of in vitro antiviral activity to the in vivo setting is crucial to identify potentially effective dosing regimens of hydroxychloroquine. In vitro 50%/90% maximal effective concentration values for hydroxychloroquine should be compared to the in vivo free extracellular tissue concentration, which is similar to the free plasma hydroxychloroquine concentration.